2010
DOI: 10.1292/jvms.09-0347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Several Pyrethroids on Hepatic Cytochrome P450 Activities in Rats

Abstract: Four commonly used pyrethroids (permethrin, bifenthrin, ethofenprox, and fenpropathrin) were orally administered to Sprague-Dawley rats for 5 days to study their effects on the liver cytochrome P450 (CYP) activities. Also Michaelis-Menten kinetics of the metabolic reactions catalyzed by liver CYPs were examined after adding these pyrethroids to the assay system to investigate their possible inhibitory effects on liver CYPs activities. These reactions included ethoxyresorufin O-deethylation, tolbutamide hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…However, the underlying mechanism by which pyrethroids induced oxidative stress is still unknown. It was reported that decreased activity of mitochondria complex I and cytochrome P450 [32], and mitochondrial dysfunction was involved in pyrethroid-induced oxidative stress [33]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanism by which pyrethroids induced oxidative stress is still unknown. It was reported that decreased activity of mitochondria complex I and cytochrome P450 [32], and mitochondrial dysfunction was involved in pyrethroid-induced oxidative stress [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of cytochrome P450 activity caused by pyrethroids has not been extensively studied. However, cis-permethrin and fenpropathrin were reported to be inhibitors of CYP1A measured on rat liver microsomes in vitro [47]. Moreover, deltamethrin was found to inhibit several hepatic cytochrome P450 activities in a fish (Cyprinus carpio L.) at a concentration equal to 0.2 mg/L during 72-h exposure and fish-liver microsome (ECOD) activity [48].…”
Section: Sublethal Effects Of A-cypermethrinmentioning
confidence: 98%
“…Abdou et al (2010) reported that ETF induced CYP1A in rats subjected to oral administration of ETF for 5 days. On the contrary, in the present study, CYP2B was induced in all of the DEN+ETF groups, while CYP1A was not induced.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in the present study, CYP2B was induced in all of the DEN+ETF groups, while CYP1A was not induced. The reason why CYP2B was not induced in the study of Abdou et al (2010) is unclear, but it is suspected that ETF has the potential to induce CYP1A in a shortterm administration, while it will have the potential to induce CYP2B and inhibit CYP1A in a long-term administration. PB induces a large spectrum of drug-metabolizing enzymes, and is a typical CYP2B inducer in rats (Waxman and Azaroff, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation